UPAYA KEPALA SEKOLAH DAN PENGAJAR MENINGKATKAN PARTISIPASI SISWA PADA ASPEK RELIGI DALAM PEMBELAJARAN DARING MASA PANDEMI DI MA BILINGUAL BATU - Muhammad Sahlan Alhanani Hamid; Khoirul Asfiyak; Muhammad Sulistiono (VICRATINA, 2021)
Meanwhile, online learning aims to carry out learning during the pandemic period which began to take effect in the 2019/2020 academic year to date in Indonesia, especially at MA Bilingual Batu, school principals and educators are trying to increase student participation, which of course has obstacles in participating in learning activities and religious programs. . In the learning process, when the researchers conducted research, where online learning during the pandemic had been running for more than a year, it had two learning methods, namely online (online) and offline (face to face). The implementation of learning is more dominant online, while offline is set up twice a week.